Development of an Arduino-Based Smart Container Tracker System - Anggun Prima Gilang Rupaka; Riz Rifai Oktavianus Sasue; Rahmat Ahmad; Hendra Yuda Novianto (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2025)
Satellite-based positioning systems are extensively used to determine observational coordinates on land, sea, air, and space by leveraging artificial satellites. The term Global Navigation Satellite System (GNSS) encompasses all satellite-based global positioning systems, either as standalone systems or in combination with other augmentation systems. Container tracking systems utilize advanced technologies to monitor and trace the movement of cargo containers during maritime transportation. These systems enable companies to optimize supply chain management, reduce the risk of cargo loss or damage, and enhance shipment security. Additionally, customers benefit from greater visibility of the status and location of goods, allowing for more effective planning. This study aims to examine the operational framework of an Arduino-based Smart Container Tracker. The research follows a Research and Development (R&D) methodology, which emphasizes the systematic development and exploration of theoretical or practical applications through innovation.